Intervention nurses in chemotherapy in women with breast cancer - Sara Gabrielly de Sousa Costa Soares, Judite Oliveira Lima Albuquerque (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v2i4.1238